Pelatihan Media Pembelajaran Digital untuk Tenaga Pendidik Di Masa Pandemi Di SMP Muhammadiyah 4 Porong Sidoarjo - Busono, Suhendro; Rosid, Moch Alfan; Rahmawati, Yunianita (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
In 2020 Indonesia goverment got the big disaster from God, It is namely Corona Virus. In education sector such as school,university and other formal education can’t do teaching learning activity directly.Teacher and student can’t do face to face activity because they are limited by goverment policy about social distancing.Education Ministry can solve the limitation of internet access bandwith by using free internet access or big bandwith, unfortunetly the big problem that can’t be solved by Indonesia Goverment is teacher have no knowladge about digital learning. Abdimas Team of Sidoarjo Muhammadiyah University try to aim this big problem. Abdimas Team of Sidoarjo Muhammadiyah University held training of digital learning for SMP Muhammadiyah 4 Porong Sidoarjo. Platform of this digital learning uses EDMODO. The result of this training is teacher and student can do teaching and learning activity periodically using internet media. The conclusion of this article is digital learning is necessary in revolution 4.0 because growth of information technology raise significantly